High-level Political Appointments in the Philippines Patronage, Emotion and Democracy - Hodder, Rupert; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2014)
This book questions the belief that patronage explains poor governance and weak organizations. Its focus is on high-level political appointees in the Philippines, but its implications for development processes and policy are far-reaching. Patronage stimulates the emergence of democracy and welfare, and constitutes formal organizations. So intimately connected is it with the health of democracy and effective organizations that attempts to eradicate patronage only harm social, organizational and democratic life. In developed societies this has meant a growing Puritanism interspersed with bouts of corruption and moral panic; and, as they seek to maintain effective organizations and vibrant democracies, a mounting desire to project their own anxieties and imperfections onto developing countries.
Introduction -- Chapter 1: Introduction - Patronage and Development -- Chapter 2: Patronage and Politics -- Chapter 3. Patronage and Appointments in the Philippines -- Chapter 4: Dimensionality -- Chapter 5: Competition -- Chapter 6: Re-casting Patronage - Organizations -- Chapter 7: Re-casting Patronage - Merit -- Chapter 8: Conclusions.
Keywords: Social sciences; Consciousness; Social Sciences; Political Communication; Public Administration; Personality and Social Psychology; Organizational Studies, Economic Sociology